Rancangan Alat Pendeteksi Benda dengan Berdasarkan Warna, Bentuk, dan Ukuran dengan Webcam - Ali Basrah Pulungan; Zhafranul Nafis (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
Along with the times, technology is also developing so rapidly, one of the innovations in technological development is the use of webcams. the use of a webcam can be developed as a sensor in detecting an object through several stages of image processing. The use of a webcam aims to simplify an automation system so that it can be used to perform several tasks at once. Therefore, the author intends to design and manufacture an object detector with measurement parameters of the object's color, shape and size. This tool uses a webcam as a sensing sensor, and uses programming in PYTHON to recognize objects to be detected, and uses a servo motor to drive object actuators. The results of this tool have been tested and are able to detect objects properly based on predetermined color, shape and size. This tool is also able to separate objects that meet specifications from objects that do not meet specifications. Object detection using a webcam and an object separating actuator can work well.